Factors influencing the age at onset in familial frontotemporal lobar dementia: Important weight of genetics. (December 2017) - Barbier, Mathieu; Camuzat, Agnès; Houot, Marion; Clot, Fabienne; Caroppo, Paola; Fournier, Clémence; Rinaldi, Daisy; Pasquier, Florence; Hannequin, Didier; Pariente, Jérémie; Larcher, Kathy; Brice, Alexis; et al.
Abstract : Objective: To quantify the effect of genetic factors and generations influencing the age at onset (AAO) in families with frontotemporal lobar dementia (FTD) due to C9ORF72 hexanucleotide repeat expansions and GRN mutations. Methods: We studied 504 affected individuals from 133 families with C9ORF72 repeat expansions and 90 FTD families with mutations in GRN, 2 major genes responsible for FTD and/or amyotrophic lateral sclerosis. Intrafamilial correlations of AAO were analyzed, and variance component methods were used for heritability estimates. Generational effects on hazard rates for AAO were assessed using mixed-effects Cox proportional hazard models. Results: A generational effect influencing AAO was detected in both C9ORF72 and GRN families. Nevertheless, the estimated proportion of AAO variance explained by genetic factors was high in FTD caused by C9ORF72 repeat expansions (44%; p = 1.10e−4), 62% when the AAO of dementia was specifically taken into account ( p = 8.10e−5), and to a lesser degree in GRN families (26%; p = 0.17). Intrafamilial correlation analyses revealed a significant level of correlations in C9ORF72 families according to the degree of kinship. A pattern of intrafamilial correlations also suggested potential X-linked modifiers acting on AAO. Nonsignificant correlation values were observed in GRN families. Conclusions: Our results provide original evidence that genetic modifiers strongly influence the AAO in C9ORF72 carriers, while their effects seem to be weaker in GRN families. This constitutes a rational to search for genetic biomarkers, which could help to improve genetic counseling, patient care, and monitoring of therapeutic trials.